Association between Arsenic Exposure and Diabetes Mellitus in Cambodia. (18th May 2014) - Huang, Jhih-Wei; Cheng, Ya-Yun; Sung, Tzu-Ching; Guo, How-Ran; Sthiannopkao, Suthipong
Abstract : Whereas studies in Taiwan found associations between arsenic exposure from drinking water and diabetes mellitus (DM), studies in other countries yielded inconsistent results, and diet might be a confounder. We conducted a study in Cambodia, where people have non-Western style diet, to evaluate the association. We measured well water and urine samples and examined skin signs of arsenicosis to assess arsenic exposure and used questionnaires to collect data on potential risk factors. We performed a fingertip blood glucose test followed by measurement of hemoglobin A1c to assess DM. The 43-male and 99-female participants had an average age of 40.4 years. We found that participants with skin signs of arsenicosis had a higher level of arsenic in the drinking water (1101.1 versus 972.2  μ g/L, P = 0.02 ). Drinking water with arsenic levels above the median (907.25  μ g/L) was associated with a nearly twofold increase in the risk of DM (odds ratio [OR] = 1.7, 95% confidence interval [CI]: 0.5–5.8), so was having skin sings of arsenicosis (OR = 1.7, 95% CI: 0.5–5.6). The ORs did not reach statistical significance most likely because of the small case number. Therefore, further studies with larger study populations are needed to confirm our findings.